DESCRIPTION OF ROLE PLAYS AS METHODOLOGICAL STRATEGY FOR TEACHING THE SPEAKING SKILL OF ENGLISH LANGUAGE WITH STUDENTS OF EIGHTH LEVEL OF EDUCACION GENERAL BASICA “A” AT UNIDAD EDUCATIVA “ISABEL DE GODIN” IN RIOBAMBA CITY, CHIMBORAZO PROVINCE, DURING THE ACADEMIC TERM 2018 – 2019. - Erazo Tapia, Miguel Angel (2020)
The main objective of the research was to analyze the use of “Role Play” to improve the speaking skill of students who studied the eighth level of Educacion General Basica “A”, at Unidad Educativa “Isabel de Godin” in the city of Riobamba, Chimborazo province, during the academic term 2018 – 2019. The research was proposed since after class observation, it was evidenced and noted that students presented some problems to initiate, maintain and conclude a clear conversation using the English language. The research is part of the qualitative approach, using the ethnographic method. For the data collection process it were used observations that were carried out during some classes and a survey applied to the teacher. The instruments were built taking into account the theoretical basis presented in the theoretical framework. The results demonstrate that the different factors used to apply “Role Play” in the activities proposed by the teacher involving oral expression were neglected at different stages of the process, so the results were not the desired. It is suggested to take pedagogical courses that must helped to students to complete the teaching-learning process, since the weaknesses detected in the application of “Role Play” did not affected only the speaking development, but also the objectives, it is advisable to maintain a good theory-based practice, it will help the teacher to improve her performance and complied the learning objectives of the students.